Terahertz spintronic magnetometer (TSM) - Agarwal, Piyush (2022)
A ferromagnetic metal consists of localized electrons and conduction electrons coupled through strong exchange interaction. Together, these localized electrons contribute to the magnetization of the system, while conduction electrons lead to the formation of spin and charge current. Femtosecond out of equilibrium photoexcitation of ferromagnetic thin films generates a transient spin current at ultrafast timescales that have opened a route to probe magnetism offered by the conduction electrons. In the presence of a neighboring heavy metal layer, the non-equilibrium spin current is converted into a pulsed charge current and gives rise to terahertz (THz) emission. Here, we propose and demonstrate a tool known as the terahertz spintronic magnetometry. The hysteresis loop obtained by sweeping terahertz (THz) pulse amplitude as a function of the magnetic field is in excellent agreement with the vibrating-sample magnetometer measurements. Furthermore, a modified transfer-matrix method employed to model the THz propagation within the heterostructure theoretically elucidates a linear relationship between the THz pulse amplitude and sample magnetization. The strong correlation, thus, reveals spintronic terahertz emission as an ultrafast magnetometry tool with reliable in-plane magnetization detection, highlighting its technological importance in the characterization of ferromagnetic thin-films through terahertz spintronic emission spectroscopy.